Identificación de Benzoilecgonina en personas detenidas en el Complejo Policial de Trujillo mediante cromatográfia de capa fina, octubre – diciembre 2018 - Bardales Chávez, Sandra Fiorella (2019)
This report includes the identification by thin-layer chromatography of benzoylecgonine in urine of persons detained in the Trujillo Police Complex, October-December 2018. 564 urine samples were evaluated, for the identification of Benzoylecgonine by the thin-layer chromatography method . It was concluded that the percentage of positive results for Benzoylecgonine of 14% of urine samples from detained persons, with a positive result for Benzoylecgonine, 49% corresponds to Trujillo, 57% corresponds to people aged between 18 and 30 years. and 97% corresponds to the sex of men